The Impact of Technology Integration on Teaching and Learning of Mathematics: A Case Study of Public Secondary Schools in South Africa - Saziwa, Themba (Journal of Ecohumanism, 2025)
This study examined the integration of technology in teaching and learning mathematics in public secondary schools in South Africa, focusing on its availability, usage patterns, and impact on academic performance. Findings confirmed that technology enhances students’ understanding and engagement through interactive and visual learning, particularly in mathematics. However, disparities in access across schools raise equity concerns. Challenges such as insufficient resources, inadequate teacher training, and systemic constraints align with broader literature on technology adoption in developing countries and the Technology Acceptance Model, which emphasizes perceived ease of use and usefulness. The results revealed a gap between the ideal technological provisions and current realities, with outdated or unavailable tools limiting effective implementation. Recommendations highlight the need for strategic policies, equitable access to ICT resources, comprehensive teacher professional development, and sustainable investment in infrastructure to optimize the role of technology in improving mathematics education outcomes.